PEMBUATAN BIOETANOL DARI LIMBAH KEJU (WHEY) MELALUI PROSES FERMENTASI FED-BATCH DENGAN Kluyveromyces marxianus - Desiyantri Siti P.; Apsari Puspita A.; Dessy Ariyanti; H Hadiyanto (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2013)
Development of bioethanol production as a renewable energy must be supported with research about finding sources of raw materials that can be converted to bioethanol product. Cheese whey is one of these raw materials. The aim of this study is to compare batch and fed-batch operation in fermentation of whey, and to determine the effect of temperature for fed-batch operation in bioethanol process. Cheese whey is by-product of the dairy industry, which contain of 4-5% lactose. Kluyveromyces marxianus is one of microorganism used to as stater during ethanol fermentation with whey as a medium. The result showed that ethanol fermentation from whey using Kluyveromyces marxianus in fed-batch system with initial pH 4,5 and temperature operation of30oC give better result than batch system. Growth rate and biomass productivity in fed-batch system are 0,186/h and 6,47 gr/Lh respectively, while for batch are 0,13/h and 4,74 gr/L h, respectively concentration and yield ofethanol for fed-batch are 7,9626 gr/L and 0,21 gr ethanol/gr substrate, for batch system are 4,6362 gr/L and0,12 gr ethanol/gr substrate. Fermentation under temperature of 30oC showed optimum growth rate and concentration of biomass which is 0,186/h and 13,4 gr/L. Maximum ethanol concentration  was achieved at7,9626 gr/L